3D printed high carbon content steel and method of preparing the same

The integration of HIP and curing processes in 3D printed ferrous alloys improves mechanical properties by optimizing carbide distribution and size, resulting in higher hardness and reduced wear rates.

JP2025011174APending Publication Date: 2025-01-23VBN COMPONENTS
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
JP2024174345
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2019-10-17
Filing Date
2024-10-03
Publication Date
2025-01-23

AI Technical Summary

Technical Problem

Existing methods for producing 3D printed iron-based alloys with high hardness are time-consuming and do not achieve optimal mechanical properties, particularly in terms of carbide size and distribution, leading to reduced wear resistance and toughness.

Method used

A method integrating Hot Isostatic Pressing (HIP) and curing processes to produce 3D printed products with a ferrous alloy matrix and carbide particles, involving specific temperature and pressure cycles to enhance carbide distribution and hardness, resulting in improved mechanical properties.

Benefits of technology

The integrated process achieves a 12% increase in hardness and a 7.5% reduction in wear rate while maintaining toughness, with carbides uniformly distributed and reduced in size, enhancing the material's performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025011174000001_ABST
    Figure 2025011174000001_ABST
Patent Text Reader

Abstract

To provide a 3D printed product of an iron-based alloy having a narrow distribution of carbide areas.SOLUTION: There is provided a 3D-printed product made of an iron-based alloy comprising a metal matrix and grains of carbides embedded in the metal matrix; wherein the alloy comprises, by weight %, carbon: 1.0 or more and 5.0 or less; chromium: 2.0 or more and 22.0 or less; iron: balance; wherein the alloy further comprises at least two of the elements: tungsten: 2 or more and 13 or less, cobalt: 7 or more and 18 or less, molybdenum: 1 or more and 10 or less, and vanadium: 3 or more and 8 or less; wherein the alloy comprises unavoidable trace amount of impurities; wherein the maximum carbide area is less than 8 μm2; wherein the average carbide area is less than 2 μm2; wherein the carbide area distribution has a difference between the d90 value and d10 value of 1.90 μm2 or less; and wherein the carbide area distribution has a d90 value of 2.20 μm2 or less.SELECTED DRAWING: Figure 12
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to 3D printed products of iron-based alloys with high hardness, which are hardened using a furnace where the product obtained from 3D printing is processed during Hot Isostatic Pressing (HIP) and quenched. [Background technology]

[0002] Today, there are several different techniques for producing powder metallurgy materials. One of the main methods is PM-HIP (powder metallurgy isostatic pressing). The technique involves spraying (granulating) metal powder, placing the powder in a container, sealing the container, and subjecting the sealed container to HIP, for example, at 1120-1150°C and 100 MPa for typically 3 hours, according to standard processes. The result is typically a consolidated block of material that needs to be further processed.

[0003] The container can have different shapes, depending largely on the material and shape required for the final part. It can also be a standard cylindrical shape if the material is rod for further manufacturing.

[0004] In the latter case, for example for the production of PM-HSS (powder metallurgy high speed steel), the material block is then typically forged and rolled to the final bar dimensions. These bars are then typically soft-tempered and then transported to inventory. They are then transported to a workshop where soft machining is performed for the shaping of the required details, such as gear hobs. However, after soft machining, the gear hob blanks are hardened in a vacuum furnace and then tempered in another furnace. And finally, the hardened blanks can be the basis for achieving the desired surface tolerances.

[0005] Typically, after machining of the softened and tempered steel bar, hardening of the material is performed. One of the most common hardening processes for PM-HSS is heating to 1180°C, remaining at that temperature during the holding period, and then cooling to 25-50°C, ensuring a minimum cooling rate of 7°C / s between 1000°C and 800°C. In this case, hardening is followed by tempering, where the material is repeatedly heated to 560°C with holding times of more than 1 hour (h) and cooled to less than 25°C between the cycles.

[0006] The temperature will of course depend on the type of alloy and the hardness target, and in addition, if precision soft machining is being performed, a stress relaxation step (typically 600-700 °C for 2 hours (h) and slow cooling to 500 °C, followed by cooling to 25 °C) can be added.

[0007] The outcome of the PM-HIP process is therefore an effect of temperature, pressure and time, besides powder quality, composition, forging and rolling.

[0008] The HIP process may also be utilized for 3D printed (additively manufactured) metal alloys. The process may then serve as a way to close pores resulting from the 3D printing process. The process may then serve to ensure full density components. After the HIP process of the 3D printed product, a conventional hardening process may then be used.

[0009] The outcome of the 3D printing, HIP and curing process is then a result of the powder quality, composition and 3D printing parameters, plus temperature, pressure and time. Nevertheless, this multi-step process is time consuming. Summary of the Invention

[0010] The object of the present invention is to overcome the drawbacks of the prior art. Thus, the present invention provides a method in which HIP and hardening are integrated and the resulting material unexpectedly has improved mechanical properties compared to conventionally HIPed and hardened materials. The present invention also aims to provide materials or products with a more uniform carbide size or carbide area distribution. For example, the hardness of the material was improved by up to 12% and wear studies revealed a 7.5% lower wear rate. Moreover, even with the increased hardness, the toughness remained similar to the conventionally processed samples. This is more pronounced for alloys with a higher carbon content.

[0011] In a first aspect, the present invention relates to a 3D printed product as claimed in claim 1.

[0012] In a preferred embodiment, the present invention provides a 3D printed product formed of an iron-based alloy comprising a metal matrix and carbide particles embedded in the metal matrix; The above alloy Carbon: weight percent not less than 1.0 and not more than 5.0; Chromium: not less than 2.0 and not more than 22.0% by weight; Iron: Balance; Including, The alloy is Tungsten: 2% or more and 13% or less by weight; Cobalt: not less than 7 and not more than 18% by weight; Molybdenum: ≥1 and ≤10% by weight; Vanadium: not less than 3 and not more than 8% by weight; and further comprising at least two of the elements: The alloy contains unavoidable traces of impurities; Maximum carbide area is 8μm 2 The average carbide area is less than 2 μm 2 Less than; and / or Carbide area distribution is 1.90μm 2 having a difference between the d90 and d10 values ​​that is equal to or less than: and / or Carbide area distribution is 2.20μm 2 For 3D printed products having the following d90 values:

[0013] In a second aspect, the present invention provides a method of making a 3D printed product, comprising: a. providing a powder of an iron-based alloy, the iron-based alloy further comprising carbon and unavoidable amounts of impurities; b. 3D printing a product from an iron-based alloy in a free-form forming apparatus having a chamber, wherein the 3D printing is performed in a vacuum; c. The product obtained in step b. i. placing the product in a furnace; ii. heating the product to a first temperature of at least 850°C, increasing the pressure in the furnace to a first pressure of at least 80 MPa, and holding the product at the first temperature and first pressure for a first holding time; iii. heating the product to a second temperature of at least 950°C and holding the product at the second temperature and at a second pressure for a second holding time; iv. quenching the product to a third temperature, reducing the pressure in the furnace to a third pressure, and holding the product at the third temperature and the third pressure for a third hold time; v. temperature cycling by heating the product to a fourth temperature, increasing the pressure in the furnace to a fourth pressure, and holding the product at the fourth temperature and fourth pressure for a fourth hold time, and then decreasing the temperature of the product to a fifth temperature. Step of processing by The present invention relates to a method for making a 3D printed product, including:

[0014] In a third aspect, the present invention relates to a product obtainable by the method of the present invention.

[0015] In one embodiment, the product obtained by the method of the present invention is obtained by a method in which the first temperature is between 1120 and 1150° C. and the first pressure is about 100 MPa. Preferably, the first holding time is preferably 3 hours (h).

[0016] In another embodiment, the product obtained according to the invention has a hardness measured by standard material analysis method according to SS-EN ISO 6507 by finish grinding with SiC P4000 using a 2 kg Vickers indenter on ground and polished samples.

[0017] An advantage of the present invention is that the resulting product has a hardness (HV2kg) that is at least 5% higher, preferably 7% higher, and more preferably 10% higher than a corresponding 3D printed product processed using conventional HIP and heat treatment.

[0018] All embodiments described herein are applicable in all respects unless expressly stated otherwise. Preferred embodiments of the invention are defined in the dependent claims. [Brief description of the drawings]

[0019] [Figure 1] Wear rates for material 280 with different heat treatments. The figure shows the unexpectedly lower wear volume of material 280-5 after integrated HIP and hardening treatment compared to material 280-4 after conventional HIP and heat treatment. Both use a hardening temperature of 1180°C followed by 3 x 1 hour (h) tempering at 560°C. At the final sliding distance in the test (31 m), the measured wear rates were 0.0055 mm3 for 280-4 and 0.0051 mm3 for 280-5, respectively. This corresponds to a wear rate reduction of 7.5%. [Diagram 2] SEM images of material 150 after a) conventional HIP and cure (WD=7.6 mm, EHT=10.00 kV, magnification 10.00 KX) and b) integrated HIP and cure according to the present invention (WD=6.7 mm, EHT=10.00 kV, magnification 10.00 KX). [Diagram 3] SEM images of material 150 with carbide edges marked a) after conventional HIP and hardening, and b) after integrated HIP and hardening according to the present invention. [Figure 4] SEM images of material 280 after a) conventional HIP and cure (WD=7.5 mm, EHT=10.00 kV, magnification 10.00 KX) and b) integrated HIP and cure according to the present invention (WD=5.9 mm, EHT=10.00 kV, magnification 10.00 KX). [Diagram 5] SEM images of material 280 with carbide edges marked a) after conventional HIP and hardening, and b) after integrated HIP and hardening according to the present invention. [Figure 6] SEM images of material 290 after a) conventional HIP and cure (WD=6.3 mm, EHT=10.00 kV, magnification 10.00 KX) and b) integrated HIP and cure according to the present invention (WD=4.5 mm, EHT=10.00 kV, magnification 10.00 KX). [Figure 7] SEM images of material 290 with marked carbide edges a) after conventional HIP and hardening, and b) after integrated HIP and hardening according to the present invention. [Figure 8] SEM images of material 350 after a) conventional HIP and hardening (WD=4.6 mm, EHT=10.00 kV, magnification 10.00 KX) and b) integrated HIP and hardening according to the present invention (WD=4.5 mm, EHT=10.00 kV, magnification 10.00 KX). The larger grey areas are of type (Cr,V)C carbides and the smaller round, whiter particles are of type V,N enriched carbides / nitrides. [Figure 9] SEM images of material 350 with carbide edges marked a) after conventional HIP and hardening, and b) after integrated HIP and hardening according to the present invention. [Figure 10] FIG. 1 is a schematic diagram of the effect on carbide area distribution of the present invention (dotted line) compared to conventional HIP and hardening (solid line). [Figure 11] Schematic diagram of the method according to the invention. [Figure 12] Graph showing the reduction in d90 and d10 values ​​of char area distribution, in percentage, when using the present invention. [Figure 13] Graph showing carbide area distribution for samples made using conventional HIP and heat treatment and samples made using the present invention (URQ). The graph shows the difference in d90 and d10 values ​​for white and gray carbides and the average value of said differences. [Figure 14] Graph showing carbide area distribution for samples made using conventional HIP and heat treatment and samples made using the present invention (URQ), where Max represents the maximum carbide area and SD represents the standard deviation. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0020] In this application, the terms three-dimensional printing or 3D printing or freeform or additive manufacturing refer to the same thing and are used interchangeably.

[0021] In this application, the term "carbide size" refers to the widest cross-sectional area of ​​a carbide or carbide cluster.

[0022] In this application, the term "carbide area" refers to the cross-sectional area of ​​a carbide.

[0023] In this application, the term "carbide cluster area" refers to the cross-sectional area of ​​a carbide cluster. A carbide cluster is an individual carbide that is arranged close together so that it acts as one larger carbide.

[0024] In this application, the term "average carbide area" refers to the average cross-sectional area of ​​the carbides.

[0025] In this application, the term "average carbide cluster area" refers to the average cross-sectional area of ​​the carbide clusters.

[0026] In this application, the term "maximum carbide area" means that a maximum of 10% of the carbides have an area equal to or greater than this value, preferably a maximum of 5% and more preferably a maximum of 1%.

[0027] In this application, the term "maximum carbide size" means that a maximum of 10% of the carbides have this size or more, preferably a maximum of 5% and more preferably a maximum of 1%.

[0028] 3D printing products It is an object of the present invention to provide a three-dimensional (3D) printed object formed of or including an iron-based alloy having high hardness and good high temperature properties. The alloy includes a metal matrix and carbide particles incorporated within the metal matrix. The alloy is iron (balance Fe) based, includes carbon and chromium, and may further include tungsten, cobalt, vanadium, molybdenum, and carbon. Preferably, the alloy has a very low oxygen content, preferably an oxygen content of 100 ppm or less by weight, more preferably less than 50 ppm by weight.

[0029] The alloy of the present invention comprises carbon, chromium, and (balance) iron, and at least two of tungsten, cobalt, molybdenum, and vanadium. In a preferred embodiment, the alloy comprises tungsten, molybdenum, and vanadium. In another preferred embodiment, the alloy comprises tungsten, cobalt, molybdenum, and vanadium.

[0030] The chromium (Cr) content is ≧2.0 and ≦22 wt%. In a preferred embodiment, the content is 3-10, preferably 3.5-4.5 wt%. In another preferred embodiment, the chromium content is 18-22 wt%, more preferably about 20 wt%.

[0031] The tungsten (W) content is 2 to 13% by weight. In a preferred embodiment, the tungsten content is 4 to 12% by weight. In a preferred embodiment, the content is preferably 6 to 11% by weight.

[0032] The cobalt (Co) content is ≧9 and ≦18 wt %. In one embodiment, the content is preferably 10-17 wt %.

[0033] The vanadium (V) content is greater than or equal to 3 and less than or equal to 8% by weight. In one embodiment, the content is preferably between 4 and 7% by weight.

[0034] The molybdenum (Mo) content is 1 to 10 wt %. In one embodiment, the content is preferably 2 to 8 wt %, more preferably 5 to 7 wt %.

[0035] The carbon (C) content is 1.0 to 5.0% by weight. In one embodiment, the carbon (C) content is preferably 1.4 to 3.0% by weight, more preferably 2.20 to 2.60% by weight, and more preferably 2.30 to 2.50% by weight.

[0036] Besides unavoidable impurities, the remainder of the alloy is iron, i.e. Fe balance. The amount of iron in the balance depends on the amount of other components. Usually, the amount of iron is 50-70% by weight, preferably 60-65% by weight. The oxygen content in the 3D printed product should be as low as possible. In the present invention, the oxygen content is preferably 30 ppm or less, or 20 ppm or less.

[0037] The alloy may further contain unavoidable amounts of impurities or trace amounts of other elements, which may be, but are not limited to, niobium, nickel, manganese, silicon, boron, tantalum, or combinations thereof. The total amount of said other elements or impurities is preferably less than 1% by weight, less than 0.5% by weight, or less than 0.05% by weight.

[0038] In a preferred embodiment, the alloy comprises: Carbon: weight percent not less than 1.0 and not more than 5.0; Chromium: not less than 2.0 and not more than 22.0% by weight; Iron: Balance; Including, The alloy is Tungsten: 2% or more and 13% or less by weight; Cobalt: not less than 7 and not more than 18% by weight; Molybdenum: ≥1 and ≤10% by weight; Vanadium: not less than 3 and not more than 8% by weight; and further comprising at least two of the elements: The above alloys contain unavoidable traces of impurities.

[0039] One advantage of the present invention is that it does not require the use of any organic binder or adhesive, and therefore the 3D printed product typically comprises a combined content of iron, vanadium, molybdenum, carbon, tungsten, chromium, and cobalt that is 95% or more by weight. In one embodiment of the present invention, the combined content of iron, vanadium, molybdenum, carbon, tungsten, chromium, and cobalt is 97% or more by weight. Preferably, the combined content of iron, vanadium, molybdenum, carbon, tungsten, chromium, and cobalt is 98% or more by weight. More preferably, the combined content of iron, vanadium, molybdenum, carbon, tungsten, chromium, and cobalt is 99% or more by weight. Most preferably, the combined content of iron, vanadium, molybdenum, carbon, tungsten, chromium, and cobalt is 99.9% or more by weight. In one embodiment of the present invention, the amount of organic compounds in the 3D printed product is 0.1% or less by weight. Preferably, the amount of organic compounds in the 3D printed product is 0.05% by weight or less. In one embodiment of the present invention, the product is essentially free of any organic compounds. Carbon in the product is primarily present in the form of carbides, such as tungsten and chromium carbides, although elemental carbon and elemental tungsten may also be present in the matrix.

[0040] The multiphase alloy comprises a matrix of mainly iron, carbon, and chromium, but may also comprise cobalt, tungsten, and / or molybdenum. There are carbides of chromium, vanadium, molybdenum, and tungsten present in the matrix, i.e., CrC type, VC and WC, or W / Mo6C. Depending on the alloy composition, the carbides of the present invention may be mainly W / Mo6C and VC, with the total amount of said carbides being 20-30% by volume, preferably 22-28% by volume. The carbides of the 3D printed product are uniformly distributed (well dispersed) and the size distribution is narrow as seen in Table 3, shown diagrammatically in FIG. 10, and shown in FIGS. 12-14. The matrix may further comprise vanadium or nitrogen rich carbides / nitrides. The maximum carbide size of the 3D printed and hardened product is less than 10 μm. In one embodiment, the maximum carbide size is 8 μm or less, 5 μm or less, and preferably 3 μm or less. The average carbide size is usually 5 μm or less, or 3 μm or less, or 1 μm or less. The average carbide area is preferably 5 μm or less. 2 More preferably, it is 2 μm or less. 2 and even more preferably 1 μm or less. 2 In one embodiment, the average carbide area is less than or equal to 0.025 μm 2 More than this, but preferably 0.25 μm 2 This indicates that a narrow carbide size distribution is found in the product of the present invention. The maximum carbide area is preferably 10 μm 2 less than or equal to 8 μm, preferably 2 Less than or equal to 5μm 2 Less than or equal to 4μm 2 The small carbide size, carbide area, and maximum carbide area of ​​the product according to the invention are in part a result of the method according to the invention. The carbide area distribution is preferably less than 2.20 μm. 2 Less than 2.0 μm, preferably 2 Less than or equal to 1.8 μm, more preferably 2 Less than or equal to 1.6 μm, more preferably 2In one embodiment, the difference between the d90 and d10 values ​​is 1.90 μm 2 less than or equal to 1.70 μm, preferably 2 More preferably, it is 1.50 μm or less. 2 The following is the result.

[0041] Metal compounds containing carbides can cause the carbides to form clusters, stringers, dendrites or networks that make the material more embrittled. Typically, in these types of alloys, especially those with high chromium and carbon, chromium is present in the form of Cr7C3 and Cr 23 C6, but also other stoichiometric types) form carbides. These carbides typically grow rapidly during the solidification stage, which results in large and long stringers with dimensions of 100-1000 μm in size. These large carbides reduce the macro-fracture toughness and fatigue resistance in the material. Thus, one of the advantages of the present invention is that the 3D products generally contain carbides or carbide particles that are smaller than those found in the prior art and well dispersed in the matrix. This is a result of the method according to the present invention.

[0042] One advantage of the present invention is the realization of improved mechanical properties of 3D printed products. The hardness of the hardened product (austenitized at 1180°C, followed by 1 hour (h) tempering at 560°C three times, and then air-cooled at temperatures below 25° between temperature steps) can be at least 1050 HV2kg (HV2), such as at least 1075 HV2kg, or at least 1100 HV2kg, or at least 1125 HV2kg. In some embodiments, the hardness is 1075-1175 HV2kg or 1100-1150 HV2kg. The hardness is determined using a 2 kg Vickers indentation (HV2).

[0043] Without being bound by theory, it is believed that the mechanical properties of the present invention are the result of the microstructure of the product. The 3D printed product is essentially free of carbide dendritic structures. The carbides are small in size and are uniformly distributed within the matrix as can be seen in the figure. There are no or very few carbides with a size of 15 μm or more, which is typical of alloys in 3D printed and hardened products. Instead, the average size of the carbides is 10 μm or less, or 5 μm or less.

[0044] The present invention not only facilitates the creation of products and components with improved mechanical properties, but also allows the creation of products with advanced or complex three-dimensional shapes and forms. The products may comprise multiple cavities, multiple channels, or multiple holes, and the products may have curved multiple sections or multiple helical forms. These shapes or forms are created without any removal of alloy other than any post-processing. The multiple cavities, multiple holes, or multiple channels may be curved, i.e., their surfaces may be curved, helical, helical, etc. In some embodiments, the products include cavities that are sealed or have openings whose diameter or width is less than the diameter or width of the underlying cavity. The products may be cutting tools such as milling cutters, shaper cutters, power skiving cutters, drills, milling tools, etc., forming tools such as extrusion heads, wire drawing dies, hot rolling rolls, etc., or wear components such as pump or valve components, sliding or rolling bearing rings, etc.

[0045] method The method is shown diagrammatically in FIG. The present invention also relates to a method of making a 3D printed product from an alloy powder, including a combined HIP and hardening process. The alloy is an iron-based alloy (Fe balance) further including carbon and unavoidable amounts of impurities. The alloy may further include at least one of chromium, tungsten, cobalt, vanadium, and molybdenum. In a preferred embodiment, the iron-based alloy includes carbon, chromium, vanadium, and molybdenum. In another preferred embodiment, the iron-based alloy includes carbon, tungsten, chromium, cobalt, vanadium, and molybdenum. In yet another preferred embodiment, the iron-based alloy includes carbon, tungsten, chromium, vanadium, and molybdenum.

[0046] In yet another preferred embodiment, the alloy is as defined above. The alloy may be iron-based (Fe balance), comprised of carbon and chromium, and further comprised of tungsten, cobalt, vanadium, molybdenum, and carbon. In one embodiment, the alloy is iron-based (Fe balance), comprised of carbon and chromium, and further comprised of at least two of the elements tungsten, cobalt, vanadium, and molybdenum. Preferably, the alloy has a very low oxygen content, preferably less than 100 ppm by weight, more preferably less than 50 ppm by weight.

[0047] The carbon content of the iron-based alloy may be 0.2 or more and 5 or less by weight. In one embodiment, the carbon content is 2.20 or more and 2.60 or less by weight. In a preferred embodiment, the content is 2.30-2.50 by weight. In one embodiment, the carbon (C) content is 1.0 or more and 5.0 or less by weight. In one embodiment, the content is preferably 1.4 or more and 3.0 or less, more preferably 2.20-2.60 by weight, and more preferably 2.30-2.50 by weight.

[0048] The chromium content may be ≧2 and ≦30 wt%. In one embodiment, the chromium (Cr) content is ≧2.0 and ≦22 wt%. In a preferred embodiment, the content is 3.8-4.4 wt%, preferably 3.9-4.3 wt%. In a preferred embodiment, the content is 3-10 wt%, preferably 3.5-4.5 wt%. In another preferred embodiment, the chromium content is 18-22 wt%, more preferably about 20 wt%.

[0049] The tungsten (W) content may be 2 or more and 25 or less by weight. In a preferred embodiment, the content is 5 or more and 13 or less by weight. In a preferred embodiment, the tungsten content is 4-12% by weight. In a more preferred embodiment, the content is 6-11% by weight. In one embodiment, the tungsten (W) content is 2 or more and 13 or less by weight. In a preferred embodiment, the content is preferably 6-11% by weight.

[0050] The cobalt (Co) content may be 5 or more and 25 or less by weight. In one embodiment, the content is 9 or more and 18 or less by weight. In a more preferred embodiment, the content is 10-17% by weight. In one embodiment, the cobalt (Co) content is 7 or more and 18 or less by weight. In a preferred embodiment, the content is 9 or more and 18 or less by weight. In one embodiment, the content is preferably 10-17% by weight.

[0051] The vanadium (V) content may be 2 or more and 15 or less by weight. In a preferred embodiment, the content is 5 or more and 8 or less by weight. In a more preferred embodiment, the content is 6-7% by weight. In one embodiment, the vanadium (V) content is 3 or more and 8 or less by weight. In one embodiment, the content is preferably 4 or more and 7 or less by weight.

[0052] The molybdenum (Mo) content may be 2 or more and 20 or less by weight. In a preferred embodiment, the content is 3 or more and 10 or less by weight. In a more preferred embodiment, the content is 4-8% by weight, more preferably 5-7% by weight. In one embodiment, the molybdenum (Mo) content is 1 or more and 10 or less by weight. In one embodiment, the content is preferably 2-8% by weight, more preferably 5-7% by weight.

[0053] Besides unavoidable impurities, the remainder of the alloy is iron, i.e., Fe balance. The amount of iron in the balance depends on the amount of other components. Usually, the amount of iron is 50-70% by weight, preferably 60-65% by weight. The oxygen content in the 3D printed product should be as low as possible. In the present invention, the oxygen content is preferably 30 ppm or less, or 20 ppm or less.

[0054] The alloy may further comprise unavoidable amounts of impurities or trace amounts of impurities of other elements, which may be, but are not limited to, niobium, nickel, manganese, silicon, boron, tantalum, or combinations thereof. The total amount of said other elements or impurities is preferably less than 1 wt%, less than 0.5 wt%, or less than 0.05 wt%.

[0055] In a preferred embodiment, the alloy comprises: Carbon: weight percent not less than 1.0 and not more than 5.0; Chromium: not less than 2.0 and not more than 22.0% by weight; Iron: Balance; Including, The alloy is Tungsten: 2% or more and 13% or less by weight; Cobalt: not less than 7 and not more than 18% by weight; Molybdenum: ≥1 and ≤10% by weight; Vanadium: not less than 3 and not more than 8% by weight; and further comprising at least two of the elements: The above alloys contain unavoidable traces of impurities.

[0056] The oxygen content in the 3D printed product should be as low as possible, preferably below 30 ppm or below 20 ppm.

[0057] 3D printing Reference is now made to FIG. 11. The method uses a free-form apparatus (3D printer) having a chamber in which the powder is placed. The free-form method comprises obtaining a powder of an iron-based alloy (step 10) and 3D printing said powder (step 12). This is done by forming a layer of powder of the alloy in a low-oxygen environment in the chamber, as defined below. The 3D printing method may be performed as described in WO 2018 / 169477, which is incorporated herein by reference, or based on the method described in WO 2018 / 169477. One suitable free-form apparatus is an electron beam machine (EBM) by the company Arcam, such as the ARCAM A2X. The alloy comprises carbon, tungsten, molybdenum, chromium, vanadium, and cobalt, in the amounts mentioned above, the choice of alloy depending on the desired properties of the final product. The content of oxygen and other impurities in the reactor should be as low as possible, such as 10 ppm or less (corresponding to gas purity grade 5) or 1 ppm or less (corresponding to gas purity grade 6), and the environment in the reactor may include an inert gas such as argon or helium. The vacuum pressure in the reactor is 1.5×10 -3 mBar or less, preferably 1.5×10 -4 In one embodiment, the initial pressure in the reactor is about 1.10×10 -5 mBar(1.10×10 -3 Pa), and then the pressure is 1.5×10 -3 mBar or less, or preferably 1.5 x 10 -4An inert gas such as helium or argon is added to increase the pressure to below mBar. The powder is then locally melted by exposing it to an energy beam for a period of time sufficient to melt it. The energy beam can be a laser beam or an electron beam. The beam is swept across the powder in any pattern. The duration of the sweep can range from a few milliseconds to a few minutes depending on the alloy and the size of the particles in the powder. The molten powder is then allowed to solidify, at least in part, into a multi-layered metal alloy. Another layer of powder can then be added on top of the solidified alloy.

[0058] To avoid crack formation in the product and to improve the properties of the product, the product is maintained at an elevated temperature (first elevated temperature) during printing or forming of the 3D printed product. Crack formation may be due to a combination of increased internal stress and increased material brittleness at lower temperatures. The increase in internal stress is caused by volume changes at phase transitions and also by normal thermal expansion. The elevated temperature to avoid crack formation can be 300°C or more, 400°C or more, 500°C or more, 550°C or more, 600°C or more, 700°C or more, 800°C or more, or 900°C or more, but usually 1100°C or less. For example, the base plate or worktable on which the product rests can be equipped with a heating device. Thus, the 3D printed product can exhibit a temperature gradient therein during the construction of the product. Heating of the product should be controlled during the build process so that the temperature of the built product is preferably 600°C or higher, 700°C or higher, or 750°C or higher, but typically 900°C or lower, 850°C or lower, or 800°C or lower. In one embodiment, the temperature is 720°C to 790°C, such as 780°C. The temperature should, of course, be low enough for the molten powder layer to at least partially solidify before adding a new powder layer. This not only makes the method cheaper, but also allows for a more positive impact on the microstructure.

[0059] In one embodiment, the 3D printing comprises: A. forming a layer of powder of an iron-based alloy on a bed plate in a chamber, the iron-based alloy further comprising carbon and unavoidable amounts of impurities, the powder comprising substantially spherical particles and / or substantially spherical particles; B. locally melting the powder by exposing it to an energy beam for a period of time sufficient to form a molten pool; C. solidifying the molten powder into a multiphase alloy in the molten pool; D. Optionally creating a further layer of powder on the previous layer by repeating steps i-iii, where step ii comprises disposing powder on the previous layer; Including, The product being constructed is heated and maintained at an elevated temperature during the process.

[0060] The advantage of using EBM compared to laser is that thicker powder layers can be made and powders with larger grains can be used. Carbide growth occurs during solidification of the molten material and to limit the size of the carbides, the growth time should be limited. The solidification time is mainly affected by the heat diffusion rate, the heat of solidification, and the heat diffusion distance. The solidification rate in conventional casting techniques can be increased by cooling the molten material using any suitable technique such as casting in a strongly cooled refractory mold or casting the details. Furthermore, in existing prior art cladding techniques, the cooling rate, although still high, is not high enough to prevent carbide growth or to obtain a fully dense material.

[0061] Novel integrated HIP and cure The resulting 3D printed product is then processed in an integrated HIP and hardening process. This can be preferably done using a Quintus machine equipped with Uniform Rapid Quench (URQ®). In this integrated process, the 3D printed product is placed in a suitable oven or furnace (step 14). The print is heated to a first temperature of at least 850°C and the pressure is increased to a first pressure of at least 80 MPa. The product is maintained at this temperature and pressure for a first holding time (step 16), after which the temperature is further increased to a second temperature of at least 950°C. At the second temperature, the product is maintained for a second holding time (step 18), after which it is rapidly quenched (cooled) to a third temperature and the pressure is further reduced to a third pressure (step 20). Quenching can be done by any suitable means, for example using a gas such as an inert gas. To obtain better mechanical properties and microstructure, quenching is performed at a high speed, with a cooling rate of at least 10°C / s, more preferably 20°C / s, more preferably 30°C / s, more preferably at least 40°C / s, more preferably up to 50°C / s. The product is maintained at the third temperature and pressure for a third holding time. After quenching and reduction of pressure, a temperature cycle (tempering) is performed in which the temperature is increased to a fourth temperature and the pressure is increased to a fourth pressure. The product is maintained at the fourth temperature and pressure for a fourth holding time, after which the temperature may be reduced to a fifth temperature. The pressure may be further reduced to a fifth pressure. The temperature cycle may be repeated at least once, preferably twice.

[0062] In one embodiment, the first temperature is at least 1000°C, but preferably not more than 1200°C, preferably in the range of 1100°C to 1200°C, more preferably in the range of 1120°C to 1150°C.

[0063] In one embodiment, the second temperature is at least 1050° C., preferably in the range of 1100° C. to 1200° C., more preferably in the range of 1180° C. to 1200° C. The second temperature is higher than the first temperature.

[0064] In one embodiment, the third temperature is not greater than 75° C. In the quenching step (step 20), the temperature is rapidly cooled, in one embodiment, from the second temperature to a third temperature not greater than 50° C., and the third pressure is preferably not greater than 65 MPa.

[0065] In one embodiment, the first pressure is less than 210 MPa, preferably in the range of 90 to 120 MPa.

[0066] In one embodiment, the second pressure is at least 80 MPa, preferably at least 90 MPa, or preferably at least 100 MPa, preferably less than 210 MPa, more preferably less than 150 MPa. In a preferred embodiment, the first and second pressures are the same, i.e., the pressure is not changed in step 18.

[0067] In one embodiment, the third pressure is in the range of 30 to 70 MPa, preferably 55 to 65 MPa.

[0068] In one embodiment, the fourth pressure is at least 70 MPa, preferably in the range of 70-80 MPa, and more preferably about 75 MPa.

[0069] In one embodiment, the fourth temperature is in the range of 500-600°C, preferably 550-580°C, and more preferably about 560°C.

[0070] In one embodiment, the fifth temperature is 50°C or less, and preferably in the range of 20 to 25°C.

[0071] The holding times depend on the alloy composition and thickness of the product. In a preferred embodiment, each holding time is sufficient for the product to attain a set or target temperature, or furnace temperature. In a preferred embodiment, the first holding time is in the range of 1 to 4 hours, preferably 3 hours. In one embodiment, the second holding time is in the range of 10 minutes to 60 minutes, preferably 30 minutes. In one embodiment, the third holding time is in the range of 1 second to 1 hour, or 30 seconds to 30 minutes. In another embodiment, the fourth holding time is in the range of 30 minutes to 3 hours, preferably 1 hour.

[0072] As can be seen in the examples, the products according to the invention or obtained by the method according to the invention unexpectedly have high hardness and often have intrinsic brittleness. This is unexpected compared to conventional hardening processes, since the alloys processed by conventional hardening are already hardened to their "full hardening temperature" according to conventional wisdom. That this effect is realized for different types of steel is further evident when examining and comparing the results from PM-HSS materials (M42, materials 150, 280 and 290) and a highly alloyed martensitic stainless steel (material 350).

[0073] Without being bound by theory, it is believed that the integrated HIP and heat treatment reduces the amount of large carbides. This is shown, for example, in FIG. 12, where the reduction in d90 values ​​is higher than the reduction in d10 values. FIGS. 12-14 clearly show that the present process results in a product with a narrower carbide area distribution, where the amount of large carbides is reduced more than the amount of smaller carbides. The effect of the reduction in area distribution on the white carbides, as seen in FIG. 13, is even more interesting, since the white carbides are, for example, W carbides.

[0074] All the embodiments disclosed herein should be understood to be some illustrative examples of the present invention. It will be understood that various modifications, combinations and changes can be made to the embodiments and aspects without departing from the scope of the present invention. In particular, different part solutions in different embodiments can be combined in other configurations, where technically possible. EXAMPLES

[0075] Example 1 A Quintus QIH 21 URQ machine has been used to compare separate HIP and hardening and integrated HIP and hardening for 3D printed highly alloyed materials with compositions as shown in Table 1. Four 3D printed Fe alloys are compared: three high speed steels and one martensitic stainless steel. 3D printing is essentially performed as described in WO 2018 / 169477, which is incorporated herein by reference. All four materials are first conventionally consolidated by HIP, conventionally hardened, and tempered. Samples from the exact same 3D printed batch are then processed by the novel integrated HIP, hardening, and tempering process with the same conventional hardening and tempering time and temperature settings. See Table 1.

[0076] [Table 1]

[0077] Conventional HIP parameters were heating to 1120-1150°C with a holding time of 3h (hours) and a HIP pressure of 100MPa, followed by cooling to room temperature and then releasing the pressure.

[0078] Conventional hardening was performed in a conventional vacuum furnace by heating the test part to 1180°C with a holding time of about 30 minutes, followed by rapid quenching with a cooling rate of greater than 7°C / s in the interval 970°C-800°C, followed by cooling in air to 25-50°C. The test part was then tempered three times by heating the part to 560°C with a holding time of 1 hour (h), followed by cooling to 25°C between the three temperature cycles.

[0079] The conventional HIP parameters as well as hardening and tempering are all standard procedures performed at large scale suppliers.

[0080] The novel integrated HIP, hardening and tempering process according to the present invention uses the following parameters: first, the part or product is heated to 1120-1150°C while the pressure is increased up to 100MPa. At this stage, a hold time of 3 hours (h) is maintained, followed by an increase in temperature to 1180°C with a new hold time of 30 minutes. From this stage, a rapid temperature quench to 20°C (with the pressure also dropping to 60MPa) is performed. Then, three temperature increases to 560°C (followed by increased pressure to 75MPa) are performed, which is the tempering cycle. The hold times at 560°C were each 1 hour (h), and the temperature between temperature cycles was 20°C.

[0081] The material samples are then compared in hardness and in microstructure. Hardness measurements were performed by using a 2 kg Vickers indenter on ground and polished samples according to standard material analysis methods by finish grinding with SiC P4000 in accordance with SS-EN ISO 6507. At this stage, hardness was measured on several points from multiple pieces with the same results.

[0082] After cutting of the samples from the processed pieces, the samples were further processed to facilitate carbide measurements by further polishing with 1 μm diamond for 5 minutes followed by Struers OP-S solution (40 μm SiO2 at pH 9.8), a well-known method to facilitate carbide structure analysis.

[0083] result The hardness of all samples is shown in Table 2. In general, the hardness after the integrated HIP, hardening, and tempering is unexpectedly much higher than the conventional HIP and heat treatment process: 12% higher for Material 150, 11.8% higher for Material 280, 5% higher for Material 290, and 12% higher for Material 350.

[0084] [Table 2]

[0085] The wear resistance was analyzed for 280 conventionally HIPed and heat treated materials and the same grades with the novel integrated HIP and heat treatment.

[0086] The test used to analyze wear resistance is a commercial dimple grinder (Gatan) with a grinding wheel rotating on a horizontal axis pressed against a sample rotating on a vertical axis. A diamond slurry with an average particle size of 2.5 μm was introduced into the contact before each run. A fixed load of 20 g was applied to the grinding wheel as it contacted the sample. Each test had a duration of 500 wheel revolutions totaling a total sliding distance of about 31 m. For statistical purposes, the tests were repeated three times for each sample.

[0087] Three cubes of test material were prepared with test surfaces of approximately 6 × 6 mm that were ground and polished to a surface roughness of Ra ~ 3 μm. Wear rates were given by measuring the volume of material removed (abraded) by white light optical profilometry.

[0088] The results showed a 7.5% lower wear rate for the integrated HIP and heat treated grades, even though they were hardened at the same maximum temperature of 1180°C (see Figure 1).

[0089] Carbide Calculation For the carbide size analysis, a comprehensive microstructural analysis was performed and the corresponding representative microstructures are presented here.

[0090] The most important microstructural changes are the reduction of the carbide (and / or carbide cluster) area and the narrowing of the carbide area distribution, as shown in Table 3. A general trend is revealed where the maximum carbides / clusters are much smaller and at the same time the average carbide area is larger. This suggests that the carbide area distribution is much narrower. This indicates that the toughness of the alloy is improved or at least not decreased. Because the toughness of these kinds of high hardness and highly alloyed materials is set by the "largest imperfections" in the material. These imperfections are usually some kind of impurity, oxides, large carbides or carbide clusters, but can also be grinding errors, i.e. white layers due to grinding at too high a temperature. Furthermore, the material becomes more uniform and isotropic with a narrower carbide distribution.

[0091] The microstructure was analyzed in a scanning electron microscope (SEM) as shown in the figures. The SEM was a Zeiss Ultra 55 FEG-SEM using secondary electron image mode. The primary electron energies (EHT, extra-high tension voltage) were 3, 5, and 10 keV, and the aperture used was 30 (standard) or 60 μm. The microstructure of the material showed an unexpectedly high carbide content and very fine carbides (Figures 2, 4, 6, and 8).

[0092] Carbides were calculated by taking the microstructure, for example that seen in FIG. 2, marking the boundaries of single carbides or clusters of carbides and using suitable software.

[0093] The results can be seen in Figures 3, 5, 7, and 9. The results of the carbide area and percentage calculations can be seen in Table 3.

[0094] [Table 3]

[0095] Example 2 A series of tests were performed on the samples to see how toughness (impact resistance) was affected by this method compared to conventional HIP and heat treatment.

[0096] Toughness measurements were performed by 3D printing 10 Charpy toughness bars in each direction, horizontal and vertical. After the different heat treatments tested, the bars were ground to the final test bar measurements, i.e. L x W x H = 7 x 10 x 55, + / - 0.025 mm. The surface roughness is set by the last surface grinding step, grit 4000. No notches are used on the test bars. The toughness is then measured in a 300 J Charpy tester with egg radius 2 mm at room temperature. The toughness results are given in Joules and as the average value of 10 samples.

[0097] [Table 4]

[0098] As mentioned above, the hardness of the samples increased significantly when the samples were prepared by using the integrated HIP and heat treatment according to the present invention. What was unexpected was that the toughness of the samples was somewhat the same, and the increase in hardness was usually accompanied by a decrease in toughness. Figures 12-14 show the effect on the carbide area distribution for these samples, where the white and grey carbides represent how they appear in the SEM, with the white carbides usually formed with heavy metal elements such as W, and the grey carbides usually formed with lighter metal elements such as Cr or V in several different stoichiometric amounts. The carbide area analysis was performed as above. Two products per alloy were printed, one in a horizontally lying orientation and one in a vertically standing orientation, and the values ​​shown are the average of the two products.

[0099] As can be seen in Figure 12, both the d90 and d10 values ​​are lower using the present method compared to conventional HIP and heat treatment. Furthermore, Figure 12 shows that the reduction in d90 value is greater than the reduction in d10, indicating that the present method has a more pronounced effect on reducing large carbides than on small carbides.

[0100] Figure 13 shows that the carbide area profile is narrower for samples made using the present method (URQ) than for conventional HIP and heat treatment. Furthermore, the carbide area distributions of the white and grey carbides also become more similar.

[0101] FIG. 14 shows that producing samples using the present invention (URQ) results in smaller carbides (average), smaller maximum carbides (max), and a narrower distribution (SD, standard deviation).

[0102] Example 3 Here, print tests of alloy M42 were compared between two heat treatment methods, namely, conventional 3 hour (h) HIP and hardening in a separate vacuum furnace at 1180°C, tempering 3×560°C, and an integrated HIP and heat treatment according to the present invention using the same temperature and time settings as the conventional method, but at different pressures.

[0103] The powder used was gas atomized with a size fraction of 53-150 μm, with a composition according to specification in weight percent. TIFF2025011174000006.tif1864

[0104] M42 is an ultra-high Mo steel, typically a conventional non-PM high speed steel material, conforming to standards HS2-9-1-8, AISIS M42, or EN 1.3247.

[0105] The integrated HIP and heat treatment, as mentioned above, is carried out under the following conditions: HIP at 1120℃ and 1000Bar for 3 hours (h) Temperature increased to 1180°C Quenching / hardening Tempering at 560°C and approximately 500 bar for 3 x 1 hour (h) was held.

[0106] Traditional HIP and heat treatment: In a separate HIP furnace, the mixture was HIPed at 1120-1150°C and 1000 bar for 3 hours (h). Cooled to room temperature, It is transported to a hardening company, Hardened at 1180℃, It was tempered at 560°C for 3 x 1 hour (h).

[0107] The material specification for this material (as conventional bar) allows it to be hardened to 61HRC to 68HRC (Rockwell), the latter being achieved at a hardening temperature of 1190°C + 560°C for 3 x 1 hour (h). When hardened at 1180°C, the hardness is approximately 67.6HRC. Austenitization occurs at 1050-1090°C (Erasteel material specification data).

[0108] Hardness and toughness were determined as described above.

[0109] result The conventionally hardened sample had a hardness of 945+ / -68 HV2kg, whereas the sample obtained by integrated HIP and heat treatment had a hardness of 1020+ / -69 HV2kg.

[0110] [Table 5]

[0111] This means that the method results in an 8% increase in hardness.

[0112] The toughness for the integrated HIP and heat treated samples was 13-21% lower than the conventionally processed samples. Without being bound by theory, this is believed to be a result of the lower carbon content, which means that the benefits of the integrated HIP and heat treatment are not fully realized at this time.

[0113] (summary) (1) A 3D printed article formed of an iron-based alloy comprising a metal matrix and carbide particles embedded in the metal matrix; The alloy is Carbon: weight percent not less than 1.0 and not more than 5.0; Chromium: not less than 2.0 and not more than 22.0% by weight; Iron: Balance; Including, The alloy is Tungsten: 2% or more and 13% or less by weight; Cobalt: not less than 7 and not more than 18% by weight; Molybdenum: ≥1 and ≤10% by weight; Vanadium: not less than 3 and not more than 8% by weight; and further comprising at least two of the elements: The alloy contains unavoidable trace amounts of impurities; Maximum carbide area is 8μm 2 The average carbide area is less than 2 μm 2 Less than; and / or Carbide area distribution is 1.90μm 2 having a difference between the d90 and d10 values ​​that is equal to or less than: and / or The carbide area distribution is 2.20 μm 2 having a d90 value of 3D printed products. (2) The carbon content is 1.4 to 3.0% by weight. A 3D printed product as described in (1) above. (3) The alloy is Tungsten: 2% or more and 13% or less by weight; Molybdenum: ≥1 and ≤10% by weight; Vanadium: not less than 3 and not more than 8% by weight; Optionally, Cobalt: 9% or more and 18% or less by weight Further comprising: A 3D printed product as described in (1) or (2) above. (4) The alloy is Carbon: weight percent not less than 1.0 and not more than 3.0; Chromium: not less than 2.0 and not more than 22.0% by weight; Molybdenum: ≥1 and ≤10% by weight; Vanadium: not less than 3 and not more than 8% by weight; Iron: Balance; Including, The alloy contains unavoidable trace amounts of impurities. A 3D printed product as described in (1) or (2) above. (5) The alloy is Carbon: weight percent not less than 2.20 and not more than 2.60; Tungsten: 5% or more and 13% or less by weight; Chromium: not less than 3.5 and not more than 4.5% by weight; Cobalt: ≥9 and ≤18% by weight; Molybdenum: not less than 3 and not more than 10% by weight; Vanadium: not less than 5 and not more than 8% by weight; Iron: Balance; Inevitable traces of impurities Including, A 3D printed product as described in (1) or (2) above. (6) The average carbide area is 1 μm 2 is less than A 3D printed product as described in (1) above. (7) The iron-based alloy Carbon: weight percent not less than 2.25 and not more than 2.40; Tungsten: ≥6 and ≤8 wt%; Chromium: not less than 3.5 and not more than 4.5% by weight; Cobalt: ≥9 and ≤12% by weight; Molybdenum: not less than 5 and not more than 8 weight percent; Vanadium: not less than 5 and not more than 8% by weight; Iron: Balance; The 3D printed product according to (1) above. (8) The iron-based alloy Carbon: not less than 1.2 and not more than 1.8 weight percent; Chromium: not less than 3.5 and not more than 4.5% by weight; Tungsten: not less than 2.0 and not more than 4.0 weight percent; Vanadium: not less than 3 and not more than 5% by weight; Molybdenum: not less than 1 and not more than 4 weight percent; Iron: Balance; Inevitable traces of impurities Including, A 3D printed product as described in (1) above. (9) The iron-based alloy Carbon: not less than 1.5 and not more than 2.3 weight percent; Chromium: not less than 17 and not more than 22.0% by weight; Vanadium: not less than 3 and not more than 5% by weight; Molybdenum: not less than 1 and not more than 3 weight percent; Iron: Balance; Inevitable traces of impurities Including, A 3D printed product as described in (1) above. (10) The iron-based alloy Carbon: weight percent not less than 1.0 and not more than 1.20; Chromium: not less than 2.0 and not more than 5.0% by weight; Molybdenum: not less than 7 and not more than 10% by weight; Cobalt: ≥7 and ≤9% by weight; Includes; The alloy Tungsten: ≥1.0 and ≤3.0 wt%; Vanadium: not less than 1.0 and not more than 3.0% by weight; Iron: Balance; Inevitable traces of impurities Further comprising: A 3D printed product as described in (1) above. (11) The maximum carbide area is 4 μm 2 less than or equal to 3 μm, preferably 2 A 3D printed product according to any one of (1) to (10) above, which is as follows: (12) A 3D printed product according to any one of (1) to (7) above, wherein the product has a hardness of at least 1050 HV2kg, preferably at least 1100 HV2kg. (13) A method of making a 3D printed product, comprising: a. providing a powder of an iron-based alloy, said iron-based alloy further comprising carbon and unavoidable amounts of impurities; b. 3D printing a product from said iron-based alloy in a free-form forming apparatus having a chamber, wherein the 3D printing is performed in a vacuum; c. the product obtained in step b. i. placing the article in a furnace; ii. heating the product to a first temperature of at least 850°C, increasing the pressure in the furnace to a first pressure of at least 80 MPa, and holding the product at the first temperature and first pressure for a first holding time; iii. heating the article to a second temperature of at least 950°C and holding the article at the second temperature and at a second pressure for a second holding time; iv. quenching the article to a third temperature, reducing the pressure in the furnace to a third pressure, and holding the article at the third temperature and the third pressure for a third hold time; v. temperature cycling the product by heating the product to a fourth temperature, increasing the pressure in the furnace to a fourth pressure, and holding the product at the fourth temperature and fourth pressure for a fourth hold time, and then decreasing the temperature of the product to a fifth temperature. Step of processing by Including, How to create 3D printed products. (14) The vacuum pressure is 1.5×10 -3 mBar or less, preferably 1.5×10 -4 The method according to (13) above, wherein the energy beam is preferably an electron beam and the pressure is less than mBar. (15) The method according to (13) or (14) above, wherein the first temperature is at least 1000°C but is preferably not more than 1400°C, preferably in the range of 1100 to 1200°C, more preferably in the range of 1120 to 1150°C; and the second temperature is higher than the first temperature. (16) the second temperature is at least 1050°C, preferably in the range of 1100 to 1200°C, more preferably in the range of 1180 to 1200°C; The second temperature is higher than the first temperature. The method according to any one of (13) to (15) above. (17) The method according to any one of (13) to (16) above, wherein the third temperature is 50° C. or less, and the third pressure is preferably 65 MPa or less. (18) The method according to any one of (13) to (17) above, wherein the first pressure is at least 90 MPa or less, or preferably at least 100 MPa, and preferably less than 210 MPa, and more preferably less than 150 MPa. (19) The method according to any one of (13) to (18) above, wherein the fourth temperature is within a range of 500 to 600°C, preferably 550 to 580°C, and more preferably about 560°C. (20) The method according to (18) above, wherein the first pressure is within the range of 90 to 120 MPa. (21) The method according to any one of (13) to (20) above, wherein the third pressure is within the range of 55 to 65 MPa. (22) The method according to any one of (13) to (21) above, wherein the fourth pressure is at least 70 MPa, preferably within the range of 70 to 80 MPa, and more preferably about 75 MPa. (23) The method according to any one of (13) to (22) above, wherein the fifth temperature is 50°C or lower, and preferably within the range of 20 to 25°C. (24) The method according to any one of (13) to (23) above, wherein the first retention time is within the range of 1 to 4 hours, and preferably 3 hours. (25) The method according to any one of (13) to (24) above, wherein the second retention time is within the range of 10 to 60 minutes, and preferably 30 minutes. (26) The method according to any one of (13) to (25) above, wherein the third holding time is within a range of 1 second to 30 minutes. (27) The method according to any one of (13) to (26) above, wherein the fourth retention time is within a range of 30 minutes to 3 hours, and preferably 1 hour. (28) The method according to any one of (13) to (27) above, wherein the alloy further contains at least one of chromium, tungsten, cobalt, vanadium, and molybdenum. (29) The alloy comprises: Carbon: weight percent not less than 1.0 and not more than 5.0; Chromium: not less than 2.0 and not more than 22.0% by weight; Iron: Balance; Including, The alloy is Tungsten: 2% or more and 13% or less by weight; Cobalt: not less than 7 and not more than 18% by weight; Molybdenum: ≥1 and ≤10% by weight; Vanadium: not less than 3 and not more than 8% by weight; and further comprising at least two of the elements: The alloy contains unavoidable trace amounts of impurities. The method described in (13) above. (30) The method according to any one of (13) to (27) above, wherein the step of quenching the product is carried out at a cooling rate of at least 10° C. / s, preferably at least 20° C. / s, preferably at least 30° C. / s, or at least 40° C. / s. (31) The method according to (13) above, wherein the 3D printing is A. forming a layer of powder of the iron-based alloy on a bed in the chamber, the iron-based alloy further comprising carbon and unavoidable amounts of impurities, the powder comprising substantially spherical particles and / or substantially spherical particles; B. locally melting the powder by exposing the powder to an energy beam for a period of time sufficient to form a molten pool; C. solidifying the molten powder into a multi-phase alloy in the molten pool; D. optionally creating a further layer of powder on the previous layer by repeating steps i-iii, where step ii comprises disposing the powder on the previous layer; Including, the product being constructed is heated and maintained at an elevated temperature during the process; The method described in (13) above. (32) The method according to (13) above, wherein step v, which is the step of performing temperature cycling, is repeated at least once, preferably twice. (33) The method according to any one of (13) to (32) above, wherein the second pressure is at least 80 MPa, preferably at least 90 MPa, or preferably at least 100 MPa, preferably less than 210 MPa, more preferably less than 150 MPa. (34) A product obtained by the method according to any one of (13) to (33) above. (35) The product according to (34) above, wherein the resulting product has a hardness (HV2kg) that is at least 5% higher, preferably 7% higher, and more preferably 10% higher than a corresponding 3D printed product processed using conventional HIP and heat treatment. (36) The product according to (34) or (35) above, wherein the first temperature is 1120 to 1150°C and the first pressure is about 100 MPa, preferably with a holding time of 3 hours. (37) The product described in (35) above, wherein the hardness is measured using a 2 kg Vickers indenter on ground and polished samples by standard material analysis methods by finish grinding with SiC P4000 in accordance with SS-EN ISO 6507. (38) The product according to any one of (1) to (12) or (34) to (37) above, which is a milling cutter, a shaper cutter, a power skiving cutter, a drill, a milling tool, an extrusion head, a wire drawing die, a roll for hot rolling, or a sliding or rolling bearing ring.

Claims

[Claim 1] 1. A 3D printed article formed of an iron-based alloy comprising a metal matrix and carbide particles embedded in the metal matrix; The alloy is Carbon: weight percent ≧1.0 and ≦5.0; Chromium: ≧2.0 and ≦22.0 wt.%; Iron: Balance; Including, The alloy is Tungsten: 2 to 13 weight percent; Cobalt: ≧7 and ≦18 wt %; Molybdenum: ≧1 and ≦10 wt.%; Vanadium: ≧3 and ≦8 wt.%; and further comprising at least two of the elements: The alloy contains unavoidable trace amounts of impurities; Maximum carbide area is 8 μm 2 The average carbide area is less than 2 μm 2 is less than; and / or Carbide area distribution: 1.90 μm 2 having a difference between the d90 and d10 values ​​of: and / or The carbide area distribution is 2.20 μm 2 having a d90 value of 3D printed products.